Elite Turkish greco-roman wrestlers anaerobik and aerobic power profiles - Duta, D.; Eser, M. A.; Murat, G. C.; Círciumaru, D. (Science, Movement & Health, 2025)
Aim. The aim of the study is to determine the aerobic and anaerobic strength parameters of elite level Turkish Greco-Roman wrestlers.